A METHOD TO IDENTIFY AND LOCALIZE A SINGLE HOT PARTICLE IN THE LUNGS USING AN ARRAY OF HIGH-PURITY GERMANIUM DETECTORS FOR IMPROVED ESTIMATE OF THE DEPOSITED ACTIVITY. Issue 1 (19th January 2022) - Aviv, O; Epstein, L; Fried, Y; Spitz, H B; Shonkor, S; Epstein, D; Naim, A; Yungrais, Z; Datz, H
Abstract: A new method has been developed to identify and localize a single hot particle in the lungs using an array of four high-purity germanium detectors. The method is based upon calculating a set of three count rate ratios (generated by each individual detector in the array) that are evaluated in sequence to designate whether the measured deposition can be associated with a hot particle rather than the default assumption of a uniform activity distribution. Identification and localization of the hot particle are determined from a single in vivo measurement in which detectors are positioned above and below the thorax. The method was tested using an anthropomorphic thorax phantom in which point sources of 241 Am, 137 Cs and 60 Co were individually inserted in the lungs at 15 different locations and were measured using a scanning bed whole-body counter. Depending upon source location and photon energy, a bias of −35% up to +76% could be introduced by falsely assuming a uniform activity distribution in the lungs. This bias would directly translate to an erroneous dose estimate to the lungs. It was demonstrated that by using the appropriate detector efficiencies for the single hot particle, the bias associated with the activity determination is reduced to <10% and 2% in average.